Associations of e-cigarette industry beliefs and e-cigarette use and susceptibility among youth and young adults in the United States. (1st February 2022) - Cuccia, Alison F.; Patel, Minal; Kierstead, Elexis C.; Evans, W. Douglas; Schillo, Barbara A.
Abstract: Background: Anti-industry sentiments are protective against smoking, but the relationship between industry beliefs and e-cigarette use remains unknown. Methods: A nationally representative survey of U.S. youth and young adults in Fall 2019 (n = 9554) assessed knowledge that e-cigarette and cigarette companies are the same, belief that e-cigarette companies lie about harm, and belief that tobacco companies want young people to vape. Weighted multivariate logistic regression models estimated odds of current use and susceptibility to use (among ever and never users) by industry knowledge and beliefs. Additional models assess association between industry knowledge and industry beliefs. All models controlled for harm perceptions, friend use, sensation seeking, combustible use, and demographic characteristics. Results: Disagreement that companies lie about harm (adjusted odds ratio (aOR)= 1.94, 95% CI: 1.43–2.63) and companies want young people to vape (aOR=1.72, 95% CI: 1.36–2.17) was associated with increased odds of current use. Belief that e-cigarette and cigarette companies were different entities was associated with increased odds of current use (aOR=1.45, 95% CI: 1.12–1.88). Disagreement or not knowing that companies are the same was associated with lower odds of believing companies lie about harm (disagreement aOR=0.37, 95% CI: 0.27–0.52; don't know aOR=0.47, 95% CI: 0.35–0.65) and belief that companies want young people to vape (disagreement aOR=0.36, 95% CI: 0.28–0.46; don't know aOR=0.54, 95% CI: 0.42–0.68). Conclusion: Similar to cigarettes, e-cigarette industry beliefs were associated with current use among young people. Highlighting e-cigarettes' connection to Big Tobacco may be an important strategy to prevent youth and young adult e-cigarette use. Highlights: Developing anti-industry sentiments is a key strategy in youth smoking prevention. The relationship between industry beliefs and e-cigarette use is unknown. Beliefs about the industry were associated with current e-cigarette use. Changing industry beliefs may reduce e-cigarette use among young people.